2020
DOI: 10.1002/jbmr.4137
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Scoliosis as a Rotatory Decompensation of the Spine

Abstract: Many years of dedicated research into the etiology of idiopathic scoliosis have not led to one unified theory. We propose that scoliosis is a mechanical, rotatory decompensation of the human spine that starts in the transverse, or horizontal, plane. The human spine is prone to this type of decompensation because of its unique and individually different, fully upright sagittal shape with some preexistent transverse plane rotation. Spinal stability depends on the integrity of a delicate system of stabilizers, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 79 publications
2
21
0
1
Order By: Relevance
“…The current and earlier studies again confirm the interaction between the sagittal spinal profile as dictated by the PI and the occurrence of scoliosis [1][2][3][4][5][6][7]. This strengthens the hypothesis of a causal relationship between sagittal spinal morphology and development of both idiopathic adolescent and adult degenerative scoliosis [7,[12][13][14].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The current and earlier studies again confirm the interaction between the sagittal spinal profile as dictated by the PI and the occurrence of scoliosis [1][2][3][4][5][6][7]. This strengthens the hypothesis of a causal relationship between sagittal spinal morphology and development of both idiopathic adolescent and adult degenerative scoliosis [7,[12][13][14].…”
Section: Discussionsupporting
confidence: 85%
“…The mechanical basis of scoliosis is becoming more and more understood. The human spine has a unique sagittal profile, that renders certain spinal segments prone to decompensate into a scoliotic deformity [2,4,5]. How, why and when this decompensation starts is still matter of continuing investigations, however, not yet fully understood mechanical properties of the maturing as well as the degenerating disc as the primary passive stabilizer of the spine likely play a role in the pathogenesis of scoliosis [4,25,26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have demonstrated the significant contribution of the intervertebral discs to the deformation of the spine in scoliosis [ 1 , 2 , 3 ]. For undisturbed and harmonious spinal development, rapidly increasing loads during the growth spurt require adequate maturation of the spine’s stabilizers, of which the disc is an essential component [ 4 ]. Skeletal maturity is traditionally assessed on X-rays of the iliac crest, the hand, and wrists, or other growth cartilages remote from the spine.…”
Section: Introductionmentioning
confidence: 99%